DUKUNGAN PEMERINTAH TERHADAP KINERJA GURU PAUD DI MASA PANDEMI - Lista Apriliani (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2022)
The implementation of distance learning that applies at all levels of education as an effort to prevent the transmission of covid-19 is still experiencing many obstacles, one of which is the obstacles experienced by kindergarten teachers. The government has made various efforts to overcome these problems, both through regulations, programs to improve the skills of educators, network expansion and access to learning resources during the COVID-19 emergency. This study aims to determine the extent to which the role of government assistance can support the performance of kindergarten teachers during learning during the pandemic. The method used in this research is a survey method. Research data obtained online through the media google form. The sample of this study was 116 kindergarten teachers in the Banten area. The results showed that government assistance contributed to the performance of kindergarten teachers during the pandemic. Both in terms of professional competence, pedagogic competence, personality competence and social competence, all of them showed value in the "Good" and "Very Good" categories. While the type of assistance that was received the most by kindergarten teachers in the Banten area was assistance in the form of credit or internet quota, which was 57%, while the assistance for technology facilities in the form of smartphones, laptops, or projectors was only 5%.